Specific Inhibition of VanZ-Mediated Resistance to Lipoglycopeptide Antibiotics - Sur, Vishma Pratap; Mazumdar, Aninda; Vimberg, Vladimir; Stefani, Tommaso; Androvic, Ladislav; Kracikova, Lucie; Laga, Richard; Kamenik, Zdenek; Komrskova, Katerina (International journal of molecular sciences, 2021)
Teicoplanin is a natural lipoglycopeptide antibiotic with a similar activity spectrum as vancomycin; however, it has with the added benefit to the patient of low cytotoxicity. Both teicoplanin and vancomycin antibiotics are actively used in medical practice in the prophylaxis and treatment of severe life-threatening infections caused by gram-positive bacteria, including methicillin-resistant Staphylococcus aureus, Enterococcus faecium and Clostridium difficile. The expression of vancomycin Z (vanZ), encoded either in the vancomycin A (vanA) glycopeptide antibiotic resistance gene cluster or in the genomes of E. faecium, as well as Streptococcus pneumoniae and C. difficile, was shown to specifically compromise the antibiotic efficiency through the inhibition of teicoplanin binding to the bacterial surface. However, the exact mechanisms of this action and protein structure remain unknown. In this study, the three-dimensional structure of VanZ from E. faecium EnGen0191 was predicted by using the I-TASSER web server. Based on the VanZ structure, a benzimidazole based ligand was predicted to bind to the VanZ by molecular docking. Importantly, this new ligand, named G3K, was further confirmed to specifically inhibit VanZ-mediated resistance to teicoplanin in vivo.
Keywords: mikrobiální testy citlivosti; teikoplanin; simulace molekulového dockingu; bakteriální proteiny; vankomycin; lipoglykopeptidy; Bacterial Proteins; lidé; Anti-Bacterial Agents; Vancomycin; bakteriální léková rezistence; Teicoplanin; grampozitivní bakteriální infekce; grampozitivní bakterie; Microbial Sensitivity Tests; Lipoglycopeptides; antibakteriální látky; Drug Resistance, Bacterial; Gram-Positive Bacteria; Molecular Docking Simulation; Gram-Positive Bacterial Infections; Humans